PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUDIO VISUAL TERHADAP HASIL BELAJAR PJOK SISWA KELAS III UPT SD 067246 MEDAN TAHUN PEMBELAJARAN 2025/2026 - Imel Yolanda Lumban Siantar; Joen Parningotan Purba; Dyan Wulan Sari HS; Juliana Panjaitan; Frikson Jony Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of audio-visual-based interactive learning media on physical education learning outcomes of third-grade students at UPT SD Negeri 067246 Medan in the 2025/2026 Academic Year. This study used a quantitative method with a One Group Pretest-Posttest Design. The sample consisted of 31 third-grade students, determined using a purposive sampling technique. Data on the audio-visual-based interactive learning media were obtained through questionnaires administered to students, while learning outcome data were obtained through pretest and posttest scores on basic locomotor movements. The results showed that student learning outcomes after using audio-visual-based interactive learning media experienced a significant increase. This can be seen from the average pretest score of 55.70 which increased to 80.58 in the average posttest score. In addition, the average score of the student response questionnaire regarding the use of interactive audio-visual-based learning media was 75.06, categorized as very good. The correlation test results obtained a calculated r value of 0.969, greater than the r table of 0.355, indicating a very strong relationship between interactive audio-visual-based learning media and student learning outcomes. Furthermore, the results of the hypothesis test showed that the calculated t was 21.120 while the t table was 2.045 at a significance level of 5%. Thus, the calculated t ≥ t table, so Ho was rejected and Ha was accepted. Based on these results, it can be concluded that the use of interactive audio-visual-based learning media has a positive and significant effect on students' Physical Education (PJOK) learning outcomes in the basic locomotor movement material in grade III of UPT SD Negeri 067246 Medan academic year 2025/2026.